Restauration des potentialités de sols dégradés à l'aide du zaï et des cordons pierreux à l'Ouest du Burkina Faso - Yaméogo, JT.; Somé, AN.; Lykke, AM.; Hien, M.; Nacro, HB. (Tropicultura, 2013)
Restoring Soil Potential Using Zaï and Stone-Rows in West Burkina Faso. The South-Sudanian zone of Burkina Faso experienced as other agro-climatic zones of the country problems of environmental degradation, particularly soil and natural vegetation, due high climatic variability. Soil and water conservation techniques like zaï and stone-rows were tested and adopted in the driest zones of the North. The aim of this study is to investigate the possibilities of transferring these technologies in the South- Sudanian area, located between isohyets 900 and 1100 mm to restore a ferruginous degraded soil. A completely randomized Fisher block design was used. Growth and yield of sorghum (Sorghum bicolor) were measured. Soil samples were taken and analyzed. Infiltration rate was measured with a two double ring infiltrometer. The results show that "zaï" and "zaï combined with stone-rows" are transferable in the South-Sudanian zone. They allowed a better development of the sorghum and grain yield increased by 6 and 4, respectively, compared to the control. Chemical properties of the soil were significantly improved, and the pH reached a value of approximately 6.5 in the holes of zaï. "Zaï" and "zaï combined with stone-rows" contributed to significantly improve infiltration rate of water in the soil.